THE CLINICAL UTILITY AND SAFETY OF A MODEL-BASED PATIENT-TAILORED DOSE REGIMEN OF VANCOMYCIN IN NEONATES. Issue 1 (14th December 2015) - Leroux, Stéphanie; Biran, Valérie; Lopez, Emmanuel; Madeleneau, Doriane; Jacqz-Aigrain, Evelyne; Zhao, Wei
Abstract : Background and objective: Pharmacokinetic modeling approach is often applied to evaluate antimicrobials in neonates. However, the clinical application of the model-based personalized antimicrobial therapy is still limited. Our objective is to evaluate the clinical utility and safety of the model-based patient-tailored dosing of vancomycin in neonates. Methods: A model-based vancomycin dosing calculator, which was developed using the pharmacokinetic information from our previously published population pharmacokinetic model, has been integrated into the routine clinical care in 3 NICUs (Cochin, Robert Debré and Clocheville Hospitals) between June 2012 and November 2014. The target attainment rate was selected as the endpoint for evaluating the clinical utility. The percentage of patients achieving the target concentration of vancomycin was calculated using the first TDM samples taken 6–24 hours after starting vancomycin treatment. The safety evaluation was focused on nephrotoxicity, which was evaluated based on changes in serum creatinine concentration from a baseline value obtained within the 48 hours of starting vancomycin treatment. Results: A total of 190 neonates were included. The mean of the 190 first TDM vancomycin concentrations was 20.0 mg/L (10th-90th percentiles: 13.1–27.6). After receiving patient-tailored doses, the target attainment rate was 71.6% (n=136) within the range of 15–25 mg/L (90.5%, n=172, within the range of 10–30 mg/L). None of the included patients has developed vancomycin-related nephrotoxicity. Conclusion: The present work provides an evidence-based study to demonstrate the clinical utility and safety of a model-based patient-tailored dose regimen of vancomycin in neonates. The results from population pharmacokinetic study were successfully integrated in neonatal clinical practice to individualise vancomycin therapy.